Organizational Culture, Leadership, Competency as Determinants of Employee Performance City Government of Surakarta City: Motivation as a Mediating Variable - Darmanto, Darmanto; Rahayu, Basuki Sri; Susilo, Joko (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The aim of this research is to provide empirical evidence of Organizational Culture, Leadership Competence as determinants of Surakarta City Government Employee Performance through Motivation Using the convenience sampling method, 40 respondents were selected as the sample. Then performed an analysis of the data obtained in the form of instrument test, validity test, reliability test, linearity test, path analysis, t test, F test, determination coefficient test (R²) The results of this research show that organizational culture and competence have no effect on motivation, while leadership has a significant positive effect. Organizational culture and leadership have no effect on performance, while competence has a positive and significant effect. Motivation mediates the influence of organizational culture and leadership on organizational performance but does not mediate competence Keywords: Competence, Leadership, Organizational Culture, Motivation, Performance.